Cost Management in an Agro-Industrial Company in a District of Lambayeque - Santamaria, Angie; Montaño, Yomira; Curioso, Walter; Ventura, Gustavo (Journal of Ecohumanism, 2024)
Cost management has positively impacted the accounting and tax processes of companies in Peru. The present research aimed to determine the factors in cost management in an agro-industrial company in a district of Lambayeque. The methodology was based on a quantitative approach and non-experimental design. The survey technique was used, and a Likert-type questionnaire related to the study variable was used as an instrument. These data collection means were answered by 30 workers of said company through a questionnaire of 15 questions corresponding to the study variable, which was validated by three experts on the subject. Obtaining as results, with respect to the variable, that there is a high level of factors in cost management with a percentage of 86.67%; following the dimensions such as the budget with a percentage of 86.67% at a high level; consequently, we have planning with 86.67% at a high level; finally, cost calculation with a percentage of 86.67% at a high level. Therefore, we infer that the budget, planning, and cost calculation are factors that affect cost management in an agro-industrial company in a district of Lambayeque.